ANALISIS Z-SCORE PADA BANK YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2013 - Wahyu, Dhika Setyo (Jurnal Akuntansi AKUNESA, 2014)
The purpose of this research is to know about bankruptcy prediction for bank which is listed on BEI. The method used in this research is Altman z-score with the data on bank?s annual financial statements in the period of 2011-2012. This research used 33 bank which is listed on BEI. In 2011 the bank which is have highest z-score is Bank Nationalnobu, meanwhile in 2012 the bank which is have highest z-score is Bank Pembangunan Daerah Jawa Timur. The factor which is affect the value of z-score is the low value of liabilities of a company.Keywords : z-score, bank, bankruptcy.